Studi Deskriptif: Perawatan Luka Pasien dengan Infeksi Post Operasi Laparotomi di Kabupaten Sumedang - Utami, Ressa Andriyani (Jurnal Kesehatan Holistic, 2019)
46 Laparotomy is a surgical procedure in the abdominal area to overcome health problems. The risk of infection can occur due to inadequate postoperative wound care. This study used a descriptive approach to determine the description of the implementation of wound care for postoperative laparotomy patients in Sumedang District. The study sample was 60 respondents, taken by random sampling. Measuring the implementation of wound care was used using the SOP of the Ministry of Health's Republic of Indonesia Health Care Implementation Instrument using a non-participatory observation method. The results showed that the stage of the study carried out by nurses was 44% adequate, 35% of the data analysis stage was adequate, 48% of adequate nursing planning, 32% of adequate implementation, and 80% of the evaluation and documentation stages were adequate.. This study recommends that nurses do wound care according to the SOP and the Hospital provides adequate facilities to carry out nursing actions.